2009
DOI: 10.2139/ssrn.1526565
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Benefit Incidence of Public Health Spending: Evidence from Indonesian Sub-National Data

Abstract: The Institute of Social Studies is Europe's longest-established centre of higher education and research in development studies. On 1 July 2009, it became a University Institute of the Erasmus University Rotterdam (EUR). Postgraduate teaching programmes range from six-week diploma courses to the PhD programme. Research at ISS is fundamental in the sense of laying a scientific basis for the formulation of appropriate development policies. The academic work of ISS is disseminated in the form of books, journal art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Budget constraints, ineffective public spending, and sub‐optimal public insurance coverage were identified as health financing issues at the district level. After decentralization, increased fiscal independence at the district level was recognized in the majority of districts across Indonesia . The increase allowed DHO to manage their spending and prioritize according to their local health needs.…”
Section: Resultsmentioning
confidence: 99%
“…Budget constraints, ineffective public spending, and sub‐optimal public insurance coverage were identified as health financing issues at the district level. After decentralization, increased fiscal independence at the district level was recognized in the majority of districts across Indonesia . The increase allowed DHO to manage their spending and prioritize according to their local health needs.…”
Section: Resultsmentioning
confidence: 99%
“…Although Akin, Hutchinson, and Strumpf did not find significant effect of the fiscal autonomy on health spending in Uganda, they found that as the districts progressed further into the decentralization process, they allocated less money for public goods and primary health care. A study by Kruse, Pradhan, and Sparrow found that each additional 1% increase in local revenue was associated with a 0.88% increase in total public health spending . This finding suggests that an increase in local revenue does not translate into an equal rate of increase in public health spending.…”
Section: Resultsmentioning
confidence: 99%
“…Table reports the characteristics of the articles selected for review. Sixteen different studies were identified, with the earliest one published in 2003 and the most recent one published in 2016 . The selected studies were situated in Latin America ( n = 8), Asia ( n = 5), Africa ( n = 2), and multiple countries ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are indications that the new scheme has been a qualified success, with analyses showing it has been the poor who have benefited most (Kruse et al, 2009). It has been well targeted: one study shows that 80% of those covered by Jamkesmas come from the poorest 50% of the population (Sparrow et al, 2010: 10).…”
Section: Explaining the Political Mobilisation Of Islam In Indonesia 53mentioning
confidence: 99%